Enhancing organisational decision-making through management information system - Awulor, Rita Ifeyinwa; Mallam-Obi , Rino Lucy; Chukwu, Nnnena Mary (Journal of Global Social Sciences, 2022)
The goal of a management information system is to deliver information in a timely and efficient manner to assist decision-making and other management functions. It consists of flow-processing operations based on computer data that are integrated with other procedures. This finding is also true when we take into account the exponential growth of modern business data and information. Efficient business decision-making is only possible with timely, accurate, high-quality information that is managed by qualified personnel, but in most cases, ineffective efficiency is caused by a lack of effective management information systems. Every aspect of life and human activity has been streamlined by the quick growth of information technology and telecommunications technology. To achieve high-quality decision-making at all levels of management, from the top level to the lowest, this technology must be well-organized. Information technology provides excellent options for quick and qualitative manipulation to improve the standard of decision-making preparation by organising the best and optimal database.